Residual Effect of Rice Husk Biochar on Growth and Yield of Aerobic Rice - Suswana, Suli; Maulana, Dick Dick (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Biochar is a carbon-rich solid material made by pyrolyzing agricultural residual biomass, and it decomposes much more slowly than the biomass from which it is made. Biochar has been shown to have agronomic benefits. Biochar can provide agronomic benefits for a longer period due to its persistence in the soil. The purpose of this research is to gather evidence demonstrating that biochar has a longer effect on increasing aerobic rice productivity. A pot experiment was carried out in UNINUS. The treatments were as follows: control, 20 Mg rice husk biochar (RHB), 40 Mg RHB, 50 Mg RHB, 60 Mg RHB, 10 Mg RHB + 10 Mg composted poultry litter (CPL).ha-1, 20 Mg RHB + 20 Mg CPL.ha-1, 30 Mg RHB + 30 Mg CPL.ha-1, and 30 Mg RHB + 30 Mg CPL.ha-1. Treatments were started in September 2018, and the effects were measured from February to June 2019. The findings revealed that rice husk biochar and its combination with CPL increased aerobic rice growth (plant height, number of tillers, and yield). The most effective combination rate is the application of biochar and composted poultry litter, 20 Mg RHB + 20 Mg CPL.ha-1, because it significantly extended the residual effect. The combined application increased rice productivity when compared to a single application of biochar and composted poultry. The residual effect of biochar and composted poultry litter on rice productivity was superior to fresh application.